Deployment of Technological Tools and Fight against Corruption in the Nigerian Educational Administration - Dada, Mathew Sunday; Ogunode, Niyi Jacob (MultiTech Publisher, 2024)
This paper examined the important roles technology can play in addressing the corruption programme facing the Nigerian educational sector. The paper is a position that depends on secondary data. The secondary data were collected from print and online publications. The paper concluded that technology can be used to combat corruption in the educational administration and management in Nigeria. The paper noted that technology, if applied effectively, can reduce corruption in personnel management, facility development, and procurement. The paper recommends that the government should adopt technology to fight corruption in all the ministries and agencies of governments. The government should provide and direct the use of technological facilities. The government should train staff on the use of modern technological facilities. Stakeholders in education should be encouraged to use technological facilities to report and expose corruption practices in the educational sector.